Synthesis and characterization of (Cd, Zn)S buffer layer for Cu2ZnSnSe4 solar cells. (22nd June 2017) - Messaoud, Khaled Ben; Buffière, Marie; Brammertz, Guy; Lenaers, Nick; Boyen, Hans-Gerd; Sahayaraj, Sylvester; Meuris, Marc; Amlouk, Mosbah; Poortmans, Jef
Abstract: In order to improve the electrical performances of Cu2 ZnSnSe4 (CZTSe) based solar cells, the standard CdS buffer layer was replaced by (Cd, Zn)S processed by chemical bath deposition. The morphology and composition of the (Cd, Zn)S thin films were studied as a function of [Zn]/([Zn]  +  [Cd]) ratio in the chemical bath (80, 85 and 90%). The CZTSe/(Cd, Zn)S solar cells with and without Cd partial electrolyte (Cd PE) treatment were compared to CZTSe/CdS reference devices using current–voltage and external quantum efficiency measurements. The (Cd, Zn)S thin films show a non-homogeneity of Zn distribution and phase formation, with a shift from Zn(O, OH) x to ZnS phase when increasing the deposition time and a decrease of the layers thicknesses when increasing the Zn concentration in chemical bath. A model for the growth of (Cd, Zn)S thin films is proposed. The resulting CZTSe/(Cd, Zn)S devices show an important reduction of the barrier at the hetero-interface, which is attributed to the lower density of O contamination in (Cd, Zn)S compared to CdS, inducing a lower density of deep p-type recombination centers. Despite the reduced compensation of the buffer layer, CZTSe/(Cd, Zn)S devices show a deterioration of the open circuit voltage and the fill factor with the increase of Zn content in (Cd, Zn)S. These electrical losses were avoided by Cd PE treatment prior to the deposition of (Cd, Zn)S.